2022
DOI: 10.1002/bdm.2298
|View full text |Cite
|
Sign up to set email alerts
|

Combining verbal forecasts: The role of directionality and the reinforcement effect

Abstract: Recent research has shown that when people combine verbal probabilistic forecasts from two sources, they are not simply averaged but can reinforce each other; so when two advisors both said an event was "rather likely," some listeners concluded that the event was "quite likely". Conversely, when both said the event was "rather unlikely," people concluded that it was "quite unlikely." The present studies demonstrate that the direction of this effect is not evoked by high versus low probabilities, but by the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…Participants in our studies attended to advice independence both when forecasts were in a verbal format (e.g., rather likely) and when both were in a numeric format (e.g., 70% probability). Replicating prior work (Mislavsky & Gaertig, 2022;Teigen et al, 2023), we also found evidence of a general advice format effect: When combining verbal as opposed to numeric forecasts, people's final likelihood estimates became more extreme (closer to certainty).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Participants in our studies attended to advice independence both when forecasts were in a verbal format (e.g., rather likely) and when both were in a numeric format (e.g., 70% probability). Replicating prior work (Mislavsky & Gaertig, 2022;Teigen et al, 2023), we also found evidence of a general advice format effect: When combining verbal as opposed to numeric forecasts, people's final likelihood estimates became more extreme (closer to certainty).…”
supporting
confidence: 81%
“…If the advisors had both said “unlikely”—suggesting the event will not happen—a final response that reflects even more certainty that the event will not happen would be considered more extreme. This counting—or getting more extreme—may have to do with people’s sensitivity to the directionality implied in verbal likelihood terms, as noted by Teigen et al (2023). Terms such as “likely” not only suggest (vaguely) a probability value, but they reveal a positive focus—a focus on the event’s possibility of happening (Teigen, 1988; Teigen & Brun, 1999).…”
Section: Advice Independence: Why It Should Affect Advice Combination...mentioning
confidence: 99%
“…The survey also included an unrelated task presented at the onset of the survey, where participants combined two verbal probability forecasts. The task required participants to estimate the probability of an event that was described as either “not certain” or as having “a chance” to occur by two different forecasters (more details about the method and results are reported in the work of Teigen et al, 2022a ).…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the warm room example, in many instances of everyday decision making the best explanation or solution is much more opaque. Indeed, most judgment and choice problems are characterized by myriad possible solutions, and evidence that is both voluminous and subject to differing interpretations (Teigen et al, 2023). Consider an individual who wishes to purchase barbeque sauce for an upcoming cookout.…”
Section: The Brand Positivity Effect and Trait Impulsivitymentioning
confidence: 99%